Mems In Control Tower - Ramli, Mohd Akmal (Universiti Sains Malaysia, 2018)
Industry 4.0 is a current trend of automation and data exchange in manufacturing technologies. Developing and implementing dashboards is common in large digital factories to improving the performance of productive equipment and processes. The developed dashboard intends to improve performance by efficiently providing information to the productive areas and turn this information into knowledge, plans, and actions which promote an effective production line activity and also to reduce the data collection time and improve decision making. One of the main phases, the development of the dashboard layout, was performed considering visual management and continuous improvement and also improve decision making at all stages. In order to achieve an effective dashboard, its development should consider all Key Performance Indicators (KPIs) for all work-center in the MEMS department. The results underline that different KPIs are preferred for dashboards on different hierarchy levels and different work-center. This dashboard is able to put all important data on one large screen and the decision makers can analyze the data and make quick decision making. The proposed procedure assists digital factory in achieving a dashboard to improve the performance of productive areas, improving productive information and communication and promoting a culture of continuous improvement at the production line.